2017
DOI: 10.1007/s11075-017-0391-0
|View full text |Cite
|
Sign up to set email alerts
|

The truncated Euler–Maruyama method for stochastic differential delay equations

Abstract: The numerical solutions of stochastic differential delay equations (SDDEs) under the generalized Khasminskii-type condition were discussed by Mao [15], and the theory there showed that the Euler-Maruyama (EM) numerical solutions converge to the true solutions in probability. However, there is so far no result on the strong convergence (namely in L p ) of the numerical solutions for the SDDEs under this generalized condition. In this paper, we will use the truncated EM method developed by Mao [16] to study the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 25 publications
0
61
0
Order By: Relevance
“…The following Lemma show that the truncated functions F ∆ and G ∆ preserve the generalized Khasminskii-type condition for any ∆ ∈ (0, ∆ * ] as shown Lemma 4.2 in [5] and we state it here as a Lemma for the use of this paper.…”
Section: Assumption 23mentioning
confidence: 89%
“…The following Lemma show that the truncated functions F ∆ and G ∆ preserve the generalized Khasminskii-type condition for any ∆ ∈ (0, ∆ * ] as shown Lemma 4.2 in [5] and we state it here as a Lemma for the use of this paper.…”
Section: Assumption 23mentioning
confidence: 89%
“…In Section 3, we will establish the strong convergence theory without this restrictive condition. In Section 4, we will compare our new result with the one in [8] to highlight our significant contribution in this paper. In Section 5, we will establish the stronger convergence theory for the solutions over a finite time interval and this was not discussed in [8].…”
mentioning
confidence: 99%
“…The generalised Khasminskii-type theorems established by [16,20] replace the linear growth condition with the generalised Khasminskii-type condition in terms of Lyapunov functions. The numerical solutions of SDDEs under the generalised Khasminskii-type condition were discussed by Mao [18], and the theory there showed that the Euler-Maruyama (EM) numerical solutions converge to the true solutions in probability Influenced by [19], Guo et al [8] were the first to study the strong convergence of the truncated EM method for the SDDEs under the generalised Khasminskii-type condition. In this paper, we will explain, via an example, that a main condition imposed in [8] is sometimes so restrictive that the step size would be too small for the truncated EM method to be applicable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here f (a(x, y)) ≡ f (ax, ay) for any a ∈ R, x, y ∈ R d . It is obvious that the functions f ∆ and g ∆ defined above are different from the truncated functions defined in [3].…”
Section: (24)mentioning
confidence: 99%